Metropolitan calendar in El Shincal de Quimivil (Catamarca, Argentina) - Corrado, Gustavo Manuel; Gim´énez Benítez, Sixto (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2021)
This work exposes the results obtained in the Cerro Aterrazado Occidental of the Inca site “El Shincal de Quimivil” located south of the Tawantinsuyu (Catamarca, Argentina). On this topic, two alignments were found with respect to the sunrise, which give us important dates within the Inca calendar. The Cerro Aterrazado Occidental had been a local huaca, reason why it was covered by a zigzag-shaped wall of probable Cuzco construction. Because the Cerro Occidental had been an important ceremonial space of the site, where probably, the calendarical control of the fiestas had been carried out.